Molecular Characterization and Pathogenesis of Newcastle Disease Virus Isolated from Brontok Eagle in West Java, Indonesia - Liza Angeliya; Yuli Purwandari Kristianingrum; Widya Asmara; Michael Haryadi Wibowo (Bogor Agricultural University, Indonesia, 2022)
Newcastle disease (ND) is a contagious disease in poultry and numerous birds of various ages. Eagle is considered a potential reservoir for ND transmission as a wild bird. This research was conducted to molecularly characterize Newcastle disease virus (NDV) isolated from ND cases in Brontok Eagle and analyze the pathogenesis in chicken embryos. qRT-PCR was conducted as conﬁrmation of NDV without mixing Avian Inﬂuenza (AI). Sequencing the fusion (F) and haemagglutinin-neuraminidase (HN) genes from the three NDVs was performed with a speciﬁc primer. Amino acid sequence compared with other NDV from Genbank. Pathogenicity, genetic variation, distance, and phylogenetic studies were analyzed using bioinformatics software (MEGA-X). This study analyzed pathogenesis based on lesions and distribution of viral antigens in chicken embryos infected with NDV. Observations were based on tissue lesions with HE and IHC staining. NDV isolated from three Brontok Eagles is classiﬁed as velogenic strain, virulent NDV (KRQKRF), and belonging to Genotype VII subgenotype VII.2. The NDV was detected in various organ lesions, more severe in the pulmo, trachea, proventriculus, and intestine of chicken embryos. That is still similar to the previous case reports in the ﬁeld. These results show that NDV, which infected Brontok Eagle, has similar molecular characteristics and pathogenesis in chickens. These cases could be a threat to the poultry industry. Further research, surveillance, and monitoring of wild birds are needed to obtain more NDV epidemiological information in wild birds.